(untitled) (International Journal of Scientific Trends, 2025)
This study examines how innovation and technology adoption shape SMEs’ export activity along two margins: (i) export propensity (whether a firm exports) and (ii) export intensity (share of foreign sales). Synthesizing recent evidence, we develop testable hypotheses on the roles of product and process innovation, Industry 4.0 (I4.0) technologies, and digital capabilities (e-commerce, cloud, ERP/CRM, digital payments). We propose an empirical strategy combining firm-level survey microdata with policy/quasi-experimental variation to identify causal effects. We further discuss trade-policy and finance frictions that moderate technology–export linkages. Prior meta-analytic and cross-country studies show a robust positive association between innovation and export performance, while newer work highlights digital platforms and I4.0 as accelerators—conditional on absorptive capacity and access to trade finance. Our framework yields actionable implications for SME policy: targeted digitalization support, export-oriented innovation vouchers, and de-risked trade finance can materially raise export entry and scale.